Experimental and Theoretical Insights into the Electrooxidation Pathway of Azo-Colorants on Glassy Carbon Electrode - Berrios-Guinez, C (Elsevier Ltd, 2018)
Sunset yellow, Allura red and Ponceau 4R are azo-colorants with similar chemical structures. These colorants were studied by electrochemical methods at a glassy carbon electrode in phosphate buffer solution (pH 7.0), combined with UV–Vis spectroscopic and theoretical methods to unveil their electrooxidation pathway. The electrooxidation of the azo-colorants showed an irreversible process for allura red and an electrochemical/chemical process for sunset yellow and ponceau 4R. The experimental potentials and the number of electrons involved in the oxidation process were correlated with those obtained from theoretical studies to support our findings. The characteristic bands of each colorant experimentally observed by UV–Vis were successfully assigned to specific molecular orbital transitions by theoretical calculations. According to this, the band close to 450 nm was assigned to electronic transitions centered in the azo-moiety, where spectroelectrochemical studies showed its disappearance after oxidation of the colorants. These results exposed that the azo-moiety is chemically affected by the oxidation process. The resonance structures of the colorants oxidized through the azo-moiety were confirmed by spin density analysis, suggesting the azo group as the electroactive center towards the oxidation of these colorants. In this article, we used a combined experimental and theoretical approach to provide new insights into the controversial aspects of the electrochemical oxidation of sunset yellow, allura red and ponceau 4R. As a consequence of these results, we propose a new reaction pathway involving the direct oxidation of the azo group. © 2018 Elsevier Ltd